The effect of grit on work performance and psychological wellbeing: analytical study of grit literature - Azlin, Farah; Mohamad, Mardiana (International Islamic University Malaysia, 2019)
The analytical study of grit literature has been conducted to identify the contribution of grit research in various social-cultural settings and their limitations for future research direction. A total number of 17 studies have been recognised to understand the concept of grit in the context of job performance, and individuals’ mental and psychological wellbeing. We have also identified the correlation of grit with other socio-psychological factors in order to have a better understanding on its concept. The reviewed studies were conducted through quantitative designs by using self-rated survey. In general, it was found that higher level of grit has significantly increased the work performance of personnel such as medical doctors, sportsmen, and military cadets. Consistent findings were also found for the effect of grit on psychological wellbeing of individuals. Mental health issues were found to have reduced significantly with a higher level of grittiness. Nonetheless, most of the findings from this review was unable to derive grit as a standalone concept. The variable of grit is more robust when it was correlated with another socio-psychological factors. Overall, though grit was found to have positive implications for a specific setting and population, it alarmed the issue of generalisation. As grit is an emerging concept in the literature, more concrete findings and evidences are required for a comprehensive and conclusive understanding on its implications.